Care under general anesthesia of patients with autistic spectrum - Paola da Cunha Busquet; Desirée de Jesus Portelinha; Monica Lage da Costa; Viviane de Andrade Cancio de Paula (Journal of Dental Problems and Solutions - Peertechz Publications, 2021)
Introduction: The dental treatment of an autistic patient is the most difficult and the patient's collaboration is often lacking.  Objective: Thus, the objective of this report is to present a clinical case of a non-collaborating autistic patient in which it is the only viable option for carrying out treatment under general anesthesia in a hospital environment.  Case report: Male patient, 24 years old, who was consulted for a dental appointment for the first time to assess the oral cavity. It was observed that there is a need for dental treatment and extractions. The patient was non-verbal, uncooperative and aggressive. Altered behavior control was indicated for general anesthesia for treatment dental care.  Result: All dental treatment was performed with the patient under general anesthesia, including prophylaxis with prophylactic masses, a restoration and two extractions in the upper arch and one extraction in the lower arch.  Conclusion: General anesthesia allows adult autistic patients not to cooperate to be considered effective and with quality.